2018
DOI: 10.4103/1735-5362.236837
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin mitigates cyclophosphamide-induced hepatotoxicity via suppression of oxidative stress and apoptosis in rat model

Abstract: Cyclophosphamide (CP), as a chemotherapy drug, induces hepatotoxicity through causing oxidative stress. Atorvastatin (ATV) at a low dose has antioxidant and anti-inflammatory properties. The present study was designed to investigate the protective effects of ATV against CP-induced hepatotoxicity in rat. In this experimental study, 32 rats were treated with ATV orally at a dose of 10 mg/kg for 10 consecutive days, 5 days before and 5 days after the administration of a single intraperitoneal injection of CP (150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…This study observed decreased hepatic antioxidants (GPx, CAT, GSH, SOD, and GSH) with increased MDA levels in CP-treated. This observation is in unison with earlier reports [26,27]. However, hepatic antioxidants were up-regulated whereas MDA levels were down-regulated in rats post-treated and cotreated with DEXA with most remarkable effects observed in rats pre-treated with DEXA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study observed decreased hepatic antioxidants (GPx, CAT, GSH, SOD, and GSH) with increased MDA levels in CP-treated. This observation is in unison with earlier reports [26,27]. However, hepatic antioxidants were up-regulated whereas MDA levels were down-regulated in rats post-treated and cotreated with DEXA with most remarkable effects observed in rats pre-treated with DEXA.…”
Section: Discussionsupporting
confidence: 90%
“…• This study used CP (150 mg/kg) [15] and modified dose of DEXA (1mg/kg ) [16] diluted with normal saline…”
Section: Dose Selection and Animal Treatmentmentioning
confidence: 99%
“…The excess NAPQI unbound to GSH may enter a rapid reaction with the mercapto groups of cellular proteins leading to the production of excessive ROS. Lipid peroxidation is initiated and in turn eventually results in hepatic architecture destruction, apoptosis, or necrosis ( 18 ). In the current study; besides their GSH enhancing effect, the administration of flavonoids ( 1 2 3 4 5 6 ) decreased the level of MDA that was triggered as a result of injection of a high dose of paracetamol.…”
Section: Discussionmentioning
confidence: 99%
“…The production of elevated levels of free radicals and lipid peroxidation following Merc administration could damage intracellular proteins and DNA of the kidney which finally the apoptosis occurs. This phenomenon could be characterized as the universal process of hazardous agents ( 34 ). This study emphasized the antioxidant activity of Harm along with other plants with beneficial therapeutic effects by suppressing apoptosis in hazarded tissues.…”
Section: Discussionmentioning
confidence: 99%